Rhein Improves Renal Fibrosis by Restoring Cpt1a-Mediated Fatty Acid Oxidation through SirT1/STAT3/twist1 Pathway - Xianrui Song; Zesen Du; Zhenqi Yao; Xiaoyan Tang; Mian Zhang (Molecules, 2022)
The latest progress in the field of renal fibrosis mainly focuses on the new concept of “partial epithelial-mesenchymal transition (pEMT)” to explain the contribution of renal tubular epithelial (RTE) cells to renal fibrosis and the crucial role of fatty acid oxidation (FAO) dysfunction in RTE cells for the development of renal fibrosis. FAO depression is considered to be secondary or occur simultaneously with pEMT. We explored the relationship between pEMT and FAO and the effect of rhein on them. Intragastric administration of rhein significantly improved the levels of BUN, Scr, α-SMA, collagen 1A and histopathological changes in UUO-rats. Transcriptomic and metabolomic analyses revealed that abnormal signaling pathways were involved in EMT and FAO disorders. RTE cell experiments showed that TGF-β could inhibit the activity of Cpt1a, resulting in ATP depletion and lipid deposition. Cpt1a inhibitor induced EMT, while Cpt1 substrate or rhein inhibited EMT, indicating that Cpt1a-mediated FAO dysfunction is essential for RTE cells EMT. Further studies showed that Cpt1a activity were regulated by SirT1/STAT3/Twist1 pathway. Rhein inhibits RTE cell EMT by promoting Cpt1a-mediated FAO through the SirT1/STAT3/Twist1 pathway. Surprisingly and importantly, our experiments showed that FAO depression occurs before EMT, and EMT is one of the results of FAO depression.